Diagnostic Overview of COVID-19 Patients with Comorbid Type 2 Diabetes Mellitus at Royal Prima General Hospital Medan in 2020 - Lisda Pratiwi; Wienaldi; Adrian (HM Publisher, 2021)
COVID-19 is a disease caused by infection with a coronavirus known as SARS-CoV-2. COVID-19 patients with diabetes have a poor prognosis and thus have a shorter life expectancy than those without diabetes. This is because COVID-19 causes severe lung dysfunction and inflammation. The purpose of the study is to find out the description of diagnostic of COVID-19 patients with comorbid diabetes mellitus type 2 at Royal Prima general hospital Medan in 2020. The case study design method is descriptive with a retrospective approach, the sample size of 63 patient medical records is taken by purposive sampling, a complete medical record and analyzed with descriptive statistics. Most patients were aged more than 50 years old (66.7%) and female (50.8%). With symptoms of fever (84.1%), cough (87.3%), shortness of breath (87.3%), headache (28.6%), diarrhea (9.5%), nausea (42.9%), abdominal pain (31.7%), loss of smell (20.6%). The longest hospitalization time (11-20 days) (46%). It can be concluded that the most age is > 50 years, the most gender is female and the most clinical symptoms are cough and shortness of breath.